Recommendations for initial examination, differential diagnosis, and management of concussion and other head injuries in high-level football - Feddermann-Demont, N.; Chiampas, G.; Cowie, C. M.; Meyer, T.; Nordström, A.; Putukian, M.; Straumann, D.; Kramer, E. (Scandinavian Journal of Medicine & Science in Sports, 2020)
Head injuries can result in substantially different outcomes, ranging from no detectable effect to transient functional impairments to life-threatening structural lesions. In high-level international football (soccer) tournaments, on average, one head injury occurs in every third match. Making the diagnosis and determining the severity of a head injury immediately on-pitch or off-field is a major challenge for team physicians, especially because clinical signs of a brain injury can develop over several minutes, hours, or even days after the injury. A standardized approach is useful to support team physicians in their decision whether the player should be allowed to continue to play or should be removed from play after head injury. A systematic, football-specific procedure for examination and management during the first 72 hours after head injuries and a graduated Return-to-Football program for high-level players have been developed by an international group of experts based on current national and international guidelines for the management of acute head injuries. The procedure includes seven stages from the initial on-pitch examination to the graduated Return-to-Football program. Details of the assessments and the consequences of different outcomes are described for each stage. Criteria for emergency management (red flags), removal from play (orange flags), and referral to specialists for further diagnosis and treatment (persistent orange flags) are provided. The guidelines for return to sport after concussion-type head injury are specified for football. Thus, the present paper presents a comprehensive procedure for team physicians after a head injury in high-level football.